Comprehensive Review of Radiological Applications in Cancer Detection and Monitoring - Algofinah, Abdullah Hussain Mohammed; Al Sqoor, Tariq Mohammed Abdullah; Alyami, Hamad Mohammed Abdullah; AlZaaman, Hamad Ali Hamad; Albaltheen, Madran Amer; Almahri, Mana Mahdi Mana; Alsharyah, Saleh Mohammed Mana; Al rizq, Saleh Misfer Abdullah; Alyami, Jaber Mahdi Hassan; Alarram, Abdulmajeed Mana Ali (Journal of Ecohumanism, 2024)
The use of radiological procedures for the identification, assessment, and periodic follow-up of cancer patients has expanded greatly over the last few decades by achieving high standards in the diagnosis of cancer and the planning of treatment plans. A variety of imaging technologies, ranging from x-rays, CT, MRI, and US to PET and nuclear medicine imaging, have become an integral part of oncological practice. These technologies help in the timely diagnosis of a tumour, evaluation of tumour status, and determination of the effectiveness of the treatment. This review provides insight into current developments in radiological imaging, its use in cancer diagnosis, its use in the management of cancer treatment, and the possible limitations and future of radiology in oncology.